Hubungan antara Konsumsi Makanan Kariogenik dan Risiko Kejadian Karies Gigi pada Anak Usia Sekolah di Kabupaten Tangerang - Karina Megasari Winahyu; Ahmad Turmuzi; Fauzan Hakim (Faletehan Health Journal, 2019)
Dental caries among school-age children is a health problem that often occurs, but lack of optimal treatment. One of factor that might influence dental caries is cariogenic food, which sweet and sticky. The study aimed to identify the relationships between cariogenic food consumption and risk of dental caries among school-age children. The methods of this study was descriptive analytic with cross sectional approach. The sample of this study were 163 school-age children selected by using random sampling technique. The analysis technique used was chi square. The result showed that most of respondents had high consumption of cariogenic food (55,8%) and high risk of dental caries (76,7%). It showed the relationships between consumption of cariogenic food and risk of dental caries (p-value < 0,05). The study suggest that health care provider need to prevent risk of dental caries by minimizing the consumption of cariogenic food among school-age children.